FRI0195 EFFICACY AND SAFETY OF DAPIROLIZUMAB PEGOL (DZP) IN PATIENTS WITH MODERATELY TO SEVERELY ACTIVE SYSTEMIC LUPUS ERYTHEMATOSUS (SLE): A RANDOMISED, PLACEBO (PBO)-CONTROLLED STUDY. (June 2019) - Furie, Richard; Bruce, Ian N.; Dörner, Thomas; Leon, Manuel Gustavo; Leszczynski, Piotr; Urowitz, Murray B.; Haier, Birgit; Jimenez, Teri; Barbey, Catherine; Liu, Jiajun; Stach, Christian
Abstract : Background: CD40 ligand (CD40L) regulates interactions between T cells and CD40-expressing cells including antigen-presenting cells (APC) and B cells, thereby playing a critical role in autoimmune disease pathogenesis. DZP, a PEGylated monovalent Fab' antibody fragment with specificity for CD40L, prevents CD40L engagement of CD40 and thus blocks intracellular signalling and APC activation. Objectives: To report the 24-week efficacy and safety interim data of DZP in a phase IIb, randomised, double-blind, PBO-controlled, dose-ranging study in patients with SLE (NCT02804763 ). Methods: Patients with moderately to severely active SLE (SLEDAI-2K score ≥6; ≥1 BILAG grade A or ≥2 BILAG grade B organ domain scores at screening) despite stable non-biologic standard of care treatment were randomised 1:1:1:1 to receive iv DZP 6, 24 or 45 mg/kg or PBO every 4 weeks for 20 weeks. Patients receiving corticosteroids (CS) ≥10 mg/day prednisone equivalent were required to start tapering CS by Week 4; guidance was provided, but tapering schedules were ultimately determined by the investigators. The primary objective was to establish a dose-response relationship across three doses of DZP and PBO based on BICLA response rates at Week 24. Four pre-specified dose-response models were tested by a statistical method (MCP-Mod), to determine whether any of the models fit the observed data with statistical significance (at a one-sided p≤0.05). The secondary endpoint was a pairwise comparison of BICLA response rates at Week 24. Other endpoints included the SRI-4 and BICLA response rates at 12 and 24 weeks, mean changes from baseline in SLEDAI-2K scores at 12 and 24 weeks, percentage of patients with daily CS dose ≤7.5 mg/day at 12 and 24 weeks, pharmacodynamic (PD) markers and safety. Results: 182 patients were randomised; 167 (91.8%) completed Week 24 of the study. Baseline demographics were similar across treatment groups. The primary endpoint was not met as none of the pre-specified dose-response models fit the observed BICLA response rates at Week 24 with statistical significance (p=0.06 for the most applicable model). BICLA response rates and other efficacy outcome measures at Weeks 12 and 24, were numerically higher for all DZP groups vs PBO (Table 1 ). Favourable biological effects were observed with improvements in relevant PD markers, including anti-dsDNA antibody levels, in DZP groups vs PBO. Treatment-emergent adverse events (TEAEs) and serious TEAEs were generally balanced across treatment groups (Table 2 ). More upper respiratory tract infections were observed in patients treated with DZP vs PBO; the majority were mild. We observed four thromboembolic events: one in the 24 mg/kg DZP group and three in the PBO group. Conclusion: DZP appeared to be well tolerated as TEAEs were generally balanced across the treatment groups. Numerically greater improvements relative to PBO were observed consistently across multiple efficacy endpoints and biomarkers; however, for the primary endpoint no pre-specified dose-response relationship model fit the observed BICLA response rates at Week 24 with statistical significance. The potential for deriving clinical benefit from DZP in patients with SLE warrants further investigation. Acknowledgement: Supported by UCB Pharma and Biogen. Disclosure of Interests: Richard Furie Grant/research support from: Biogen, UCB Pharma, but not in the last 12 months, Consultant for: Biogen, UCB Pharma, but not in the last 12 months, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GlaxoSmithKline, Consultant for: AstraZeneca, Eli Lilly, GlaxoSmithKline, ILTOO Pharma, MedImmune, Merck Serono, Speakers bureau: GlaxoSmithKline, UCB Pharma, Thomas Dörner Grant/research support from: Eli Lilly, Janssen, Roche, UCB Pharma, Consultant for: Eli Lilly, Janssen, Roche, UCB Pharma, Speakers bureau: Eli Lilly, Janssen, Manuel Gustavo Leon: None declared, Piotr Leszczynski Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Immupharma, Janssen Cilag, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Amgen, Berlin Chemie, Eli Lilly, Novartis, Roche, Sandoz, UCB Pharma, Speakers bureau: AbbVie, Amgen, Berlin Chemie, Eli Lilly, Novartis, Roche, Sandoz, UCB Pharma, Murray B Urowitz Grant/research support from: GSK, Consultant for: BMS, Celgene, GSK, Lilly, UCB, Birgit Haier Shareholder of: UCB Pharma, Employee of: UCB Pharma, Teri Jimenez Employee of: UCB Pharma, Catherine Barbey Shareholder of: Biogen, Employee of: Biogen, Jiajun Liu Employee of: Biogen, Christian Stach Shareholder of: UCB Pharma, Employee of: UCB Pharma